Pemanfaatan Fermentasi Batang Pisang (Gedebog) Sebagai Pakan Alternatif Ternak Sapi - Taufiq, Andi Muh; Emilia, Emilia; Nurfadillah, Nurfadillah; Permatasari, Indah; Sufardi, Sufardi; Hasmariyanti, Hasmariyanti; Angriani, Reni; Halidya, Nur; Yusri, Yusri; Idris, Idris (HORIZON: Indonesian Journal of Multidisciplinary, 2025)
Banana harvesting generates abundant waste, such as stems, which are generally left to decompose, even though they can be used as fermented livestock feed. This applied research aims to utilize banana stem waste (gedebog) through a fermentation process as a high-quality alternative feed for cattle, particularly in the Bone area. This activity uses an applied research approach combined with participatory action in the Bone region. The project partners are members of livestock farmer groups who are directly involved in the feed-making process. The main materials used are chopped banana stems mixed with fermentation ingredients such as bran, sugar, and microbial inoculants (e.g., EM4). The fermentation process is carried out in a closed environment for 7–14 days. Data are obtained through direct observation, brief interviews, livestock palatability tests, and documentation, and then analyzed using qualitative descriptive analysis. The analysis results show that processing agricultural waste from banana stems into high-quality animal feed produces very high palatability for cattle, characterized by a distinctive aroma and a high consumption rate. Group members of farmers also experienced an increase in knowledge and experience in feed provision, especially during the dry season